The ameliorative potential of platelet-rich plasma and exosome on renal ischemia/reperfusion-induced uremic encephalopathy in rats - Hani M. Abdelsalam; Alaa Samy; Engy E. A. Mosaleem; Moustafa Salaheldin Abdelhamid (Scientific Reports)
Abstract Uremic Encephalopathy results from the elevation of toxins and blood-brain barrier (BBB) disruption. Renal Ischemia/Reperfusion (I/R) injury is the principal cause of acute kidney injury and brain tissue injury. The present study was crafted to estimate the restorative impact of platelet-rich plasma (PRP) and exosome injection before the reperfusion phase on the kidney following renal I/R injury and its influence on brain tissue by tracking the histopathological, biochemical, and Doppler ultrasonography alternations in both kidney and brain tissue. Forty mature male rats were divided into five groups as follows: control, I/R, PRP, exosome, and Exosome + PRP. Renal Doppler ultrasonography was traced for all rats. Serum kidney functions and acetylcholine esterase enzyme (AchE) were evaluated. Both Gamma-aminobutyric acid (GABA) and glutamate were assessed in brain tissues. The oxidative stress (malondialdehyde), anti-oxidative (glutathione and catalase), and pro-inflammatory (Tumor necrosis factor- α and interleukin-6) markers were estimated in renal tissues. Additionally, morphometric histological examination was performed in both renal and brain tissues. Both PRP and exosome-received rats exhibited a significant improvement in both serum kidney functions and AchE compared to I/R rats. There was a 3.39-fold increase in GABA and a 2.27-fold decrease in glutamate levels in the brain tissue of PRP rats compared to the I/R rats. A significant elevation (P ≤ 0.0001) of glutathione and catalase besides a significant reduction in the expression of TNF-α and IL-6 was observed in renal tissue compared to I/R rats. A significant severe reduction (P < 0.0001) in the number of Purkinje cells, pyramidal cells in the cerebellar cortex, and the CA1 region in the hippocampus was observed in I/R rats which was significantly alleviated by both PRP and exosome. Furthermore, there was a significant improvement in Doppler parameters. PRP exerted a significant superior impact on the restoration of kidney functions and repairing uremic-induced damage in brain tissue.